2016
DOI: 10.4103/0971-4065.172228
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon monotherapy for hepatitis C virus infection in patients on hemodialysis: A single center study

Abstract: There is no published study from India on hepatitis C virus (HCV) treatment in dialysis patients. Patients on dialysis with HCV infection treated with pegylated interferon (Peg-INF) monotherapy were studied. All patients were subjected to HCV-polymerase chain reaction, viral load, genotype, and liver biopsy. Quantitative HCV-RNA was performed monthly. Patients with genotype 1 and 4 were given 12 month therapy while those with genotypes 2 and 3 were given 6 months therapy. Response was classified as per standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Handling of HCV-infected patients was previously described in detail. 10 Patients with positive anti-HCV antibodies were further investigated for their qualitative HCV RNA, HCV viral load, and HCV genotype as described previously. 10 Because of our previous experience of only 1 patient with histological cirrhosis, 11 we clinically assessed the activity of liver disease, and no patient underwent liver biopsy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Handling of HCV-infected patients was previously described in detail. 10 Patients with positive anti-HCV antibodies were further investigated for their qualitative HCV RNA, HCV viral load, and HCV genotype as described previously. 10 Because of our previous experience of only 1 patient with histological cirrhosis, 11 we clinically assessed the activity of liver disease, and no patient underwent liver biopsy.…”
Section: Methodsmentioning
confidence: 99%
“… 10 Patients with positive anti-HCV antibodies were further investigated for their qualitative HCV RNA, HCV viral load, and HCV genotype as described previously. 10 Because of our previous experience of only 1 patient with histological cirrhosis, 11 we clinically assessed the activity of liver disease, and no patient underwent liver biopsy. Before starting treatment, hemoglobin, total leukocyte count, differential leukocyte count, platelets, reticulocyte counts, and alpha fetoprotein were assessed in all patients using standard methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peginterferon based treatment is successful in achieving SVR in only about half of the patients receiving the treatment and is associated with significant side effects, which can prohibit the treatment completion. 4 Goel et al showed 58% response when ribavirin was used with peginterferon. 5 The major limitation of treating patients on dialysis with sofosbuvir based regimens is limited safety data.…”
mentioning
confidence: 99%